FAKTOR-FAKTOR YANG YANG MEMPENGARUH KECENDERUNGAN KECURANGAN (FRAUD): PERSEPSI PEGAWAI DINAS PEMERINTAH KOTA BANDAR LAMPUNG - Muhammad Luthfi; Eko Wijoyo; Kusnadi Kusnadi (Jurnal Ilmiah Akuntansi Rahmaniyah, 2018)
The purpose of this study is to analyze the perception of government employees about the impact of asymetric information, enforcement of regulations, the effectiveness of internal control, unethical behaviour, compensation suitability, and leadership style to tendency of fraud in government sector. The population of this study is 110 employees who work at financial subsector on Dinas Kota Bandar Lampung. This study is a population research, therefore the respondents of this study are all of the population. The data were obtained by questionnaire. It’s analyzed by using analyze tool smartPLS 3. The result of this study showes positive impact of asymetric information, enforcement of regulations, and unethical behaviour towards tendency of fraud on government sector, there is no impact between the effectiveness of internal control and compensation suitability towards tendency of fraud on government sector.